Study of α-Amylase Inhibitory Activity of Fractions Purified by Chromatographic Methods of the Endophytic Fungus Penicillium Brevicaule Alba-CC200 (Global Journal of Medical Research, 2023)
In this study the antidiabetic activity of purified fractions of the endophytic fungus Penicillium brevicaule alba-CC200 isolated from the plant Celosia cristata was investigated Antidiabetic activity was evaluated by inhibition of -amylase enzyme The secondary metabolites of P brevicaule alba-CC200 were partially purified by column chromatography and obtained fraction II inhibited -amylase by 91 2 High inhibitory activity was observed in fraction II and was determined to be cardiac glycosides and terpenoids by thin layer chromatography TLC and qualitative analysis This requires a more precise study of the purified fractions using high-precision chromatographic methods
Keywords: a-amylase; a-glucosidase; column chromatography; TLC; cardiac glycosides; terpenoids